Տաթևի, Ս․ Թադեի և Ս․ Ստեփաննոս Նախավկայի վանքերը ԺԹ դարի առաջին կեսին - Կոստիկյան, Քրիստինե (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
From the beginning of Qajar rule in Iran the Armenian monaste-ries of Syunik and Artaz suffered the hardships of the Russo-Persian conflict and wars for the regions of Transcaucasia. The Persian docu-ments of the Matenadaran throw light on some political and economic developments around the monasteries and help elucidate some aspects of Qajar policy as regards the Armenian sanctuaries under their rule. Tatev monastery, located in the territory subject to the khan of Karabagh had passed under the rule of Russian empire after the treaty concluded in Kurakchay in 1805 and then after the fights of the Russo-Persian war of 1804 - 1813 its annexation to Russia was confirmed by the treaty of Gulistan. The monastery served as a refuge of the Russian troops fighting for the region. The monasteries of Artaz remained under the rule of Qajar Iran after the treaty of Turkmenchay concluded in 1828, at the end of the second Russo-Persian war. The Qajar governement supported the mo-nasteries of St. Thaddeus and St. Stepannos, the apostles, and tried to keep away its Armenian followers, the inhabitants of Azerbayjan from migration to the regions passed under the rule of Russia. In spite of these attempts the major portion of the Armenians of Azerbayjan migrated. However, the Qajar powers granted some estates to the monasteries in the villages around them and protected their rights with royal decrees and other documents in order to secure their survival in later Muslim environment.
Keywords: Հայ եկեղեցու պատմություն